2020
DOI: 10.1097/im9.0000000000000023
|View full text |Cite
|
Sign up to set email alerts
|

Translation: Management of Coronavirus Disease 2019 (COVID-19): Experience in Zhejiang Province, China

Abstract: The current epidemic situation of coronavirus disease 2019 (COVID-19) still remains severe. As the National Clinical Research Center for Infectious Diseases, The First Affiliated Hospital of the Zhejiang University School of Medicine is the primary medical care center for COVID-19 in Zhejiang Province. Based on the present expert consensus carried out by the National Health Commission and National Administration of Traditional Chinese Medicine, our team summarized and established an effective treatment strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
194
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(229 citation statements)
references
References 4 publications
4
194
0
15
Order By: Relevance
“…Moreover, 16.5%, 28.8%, and 8.1% of the respondents reported moderate to severe levels of depression, anxiety, and stress [11]. Also, Xu et al demonstrated that anxiety and fear were very prevalent among patients with (2019-nCoV) [12]. In another cross sectional study, Al-Rabiaah et al studied the impacts of the Middle East respiratory syndrome coronavirus (MERS-CoV) epidemic on medical students' perception and found that all of these students experienced stress [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 16.5%, 28.8%, and 8.1% of the respondents reported moderate to severe levels of depression, anxiety, and stress [11]. Also, Xu et al demonstrated that anxiety and fear were very prevalent among patients with (2019-nCoV) [12]. In another cross sectional study, Al-Rabiaah et al studied the impacts of the Middle East respiratory syndrome coronavirus (MERS-CoV) epidemic on medical students' perception and found that all of these students experienced stress [13].…”
Section: Discussionmentioning
confidence: 99%
“…Response options were "not at all," "several days," "more than half the days," and "nearly every day," scored as 0, 1, 2, and 3, respectively. The total anxiety score was divided into (0-4) = minimal anxiety, (5-9) = mild anxiety, (10)(11)(12)(13)(14) = moderate anxiety, and > 14 = severe anxiety). The scale had an Alpha reliability coefficient of 0.824.…”
Section: Ii-self-health Perceptionmentioning
confidence: 99%
“…Due to the serious adverse effects of glucocorticoids experienced by patients with SARS-CoV infections [28,29], it is questionable whether glucocorticoids should be used to treat patients with SARS-CoV-2 infections [30,31]. Our results showed that patients who received glucocorticoids had greater improvements of chest CT score and LY count.…”
Section: Discussionmentioning
confidence: 68%
“…Besides, the in vivo study of rhesus animal model also proved the prognosis improvement of combination of IFN and ribavirin [7,8]. Loutfy et al [9] compared clinical effects of IFN α combined with glucocorticoid and independent use of glucocorticoid in treatment of SARS-CoV infection. They pointed out that the IFN α combined with glucocorticoid could shorten relieving time of lung image by 50% (P = 0 .001) and improve oxygen saturation significantly (P = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, infected patients are viewed as the source of SARS-CoV-2 and asymptomatic patients might carry the virus [9]. Short-distance respiratory spraying and direct or indirect contact are major spreading ways of SARS-CoV-2, such as mouth, nose and eye mucous membrane infection with hands.…”
Section: Discussionmentioning
confidence: 99%